Quantitative Analysis of Causative Factors of Crime: A Case Study of District Sahiwal (Pakistan) (Journal of Asian Development Studies, 2024)
It is a postindustrial society in which the dynamics of social interaction and values have changed. Due to rapid technological changes, the social relations and bounding with social norms have been weakening. The impatience, delinquency, and criminal attitude of the people are increasing daily. The research objectives of this current study were to examine the causative factors of crime in district Sahiwal and to identify the elements that shape and influence criminal behavior in the region. The researcher used the quantitative method and exploited purposive sampling. The data was gathered from 120 criminals from Central Jail, Sahiwal, Pakistan. The analysis used Statistical Package for the Social Sciences (SPSS) to uncover significant patterns and relationships of variables. It was found that low socio-economic status and less academic qualification were the real causes of crime in the studied area. Based on the results, it is suggested that addressing the underlying issues of bad company, poverty, unemployment, and lack of education and strengthening legal and social frameworks can create a safer, more stable community in Sahiwal. The study's findings emphasize that only through targeted interventions that address both the symptoms and the root causes of crime can meaningful progress be made in reducing crime rates and improving the quality of life for the residents of district Sahiwal. The concerned institutions should collaborate with the concerned institutions to uplift the socio-economic status of the people, and strict law and order should be enforced to tackle deviance and crime in Sahiwal, Pakistan.